Política e Comunicabilidade: Diálogo entre Kant e Hannah Arendt - SILVA, Nildo Francisco da (2023)
This bibliographical research, of an interdisciplinary nature, uses the hermeneutic method in order to approach the convergence between politics and communicability from a dialogue between the thought of Immanuel Kant and the political theory of Hannah Arendt. Discussing, therefore, the political aspect of Kant's critical work, locating it within the scope of the Philosophy of Law, contextualizing it historically and philosophically, dealing with transcendental freedom, as well as the coexistence of freedoms in the politic body. Presenting the relationship between aesthetic judgment and communicability in the third Critique of Kant, it identifies the operation of the faculty of judging (Uteilskraft) and its relationship with the other faculties of the mind, namely, understanding (Verstand) and reason (Vernunft). Once these relationships are verified, the essential characteristics of the judgment of taste are examined, as well as the maxims of common understanding, and the sensus communis is highlighted as the foundation of communication. It then investigates the political scope of the Kantian aesthetic judgment, based on Hannah Arendt's understanding, questioning, in this thinker, the place of politics among the dimensions of Vita Activa and the deepening of politics from the aesthetic judgment Kantian, verifying how Arendt appropriates this concept, making a reading of the aesthetic judgment in its fundamental relationship with the common world and, therefore, with the scope of communication between political agents. In addition, the fundamental characteristics of the aesthetic judgment as a political judgment in Arendt's thought are verified, highlighting the role of the sensus communis, of the imagination as an active ability of the mind in the process of judging and the point of view, in the judgment, of both the actor and the spectator.